Sistem Informasi Manajemen Persediaan Roti Menerapkan Metode First In First Out (FIFO) - Putri Paramadina Tanjung; Ali Ikhwan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
These days, many companies are very attached to the existence of Management Information Systems that make it easier for companies to organize and manage business activities to make good decisions. Raihan Bakery is a business engaged in the culinary field and now there are several other branch stores scattered in the Medan city area. In the production process, cakes and other products are only produced at the main branch store which will later be supplied to other branch stores. Therefore, when a branch store runs out of inventory, the store must order again to be sent immediately. This often overwhelms the production admin which results in slow performance due to incorrect inventory information, overlapping orders and late supply of goods. Therefore, Raihan Bakery needs a Management Information System that can monitor incoming and outgoing product inventory data for both finished products and raw materials as well as leftover and expired products to ensure and adjust the inventory is correct and in accordance with its physical state so that branch store orders can be processed immediately and then supplied properly quickly and precisely. The research method used in this system is the FIFO method where the first product in is the first out. This system produces a solution in sorting out which products are worth sending first so that they can maintain product quality and can be sent immediately on time and minimize the accumulation of leftover or expired products in order to minimize losses in business